Environmental management in Fiji : a socio-political exploration of global, regional and state dynamics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Turnbull, Iéré Jane (Massey University, 2001)
The techniques of environmental impact assessment, environmental planning and protected areas are manifestations of the cultural modernisation of western society with its growth of rationality, bureaucratisation and the centrality accorded to science. Environmental impact assessment and planning techniques are also part of a growing international perspective on environmentalism that is moving towards common environmental standards and policies. The concept of formally protected areas is being subsumed into this globalist perspective, part of a scientifically-based discourse that argues loss of biodiversity is a global issue requiring a global solution. Global environmentalism accounts for the way the South Pacific Regional Environment Programme (SPREP) promotes these modern environmental management techniques to relatively undeveloped Pacific island countries. It also accounts for the way that SPREP's discourse normalises the involvement of outsiders in Pacific island environmental management. But neither global environmentalism nor cultural modernisation account for the limited way that the state in Fiji, one the most developed Pacific island countries, has practised these techniques. Neither does the search for sustainable development, topical amongst the development assistance agencies funding environmental projects in the South Pacific. The Fijian state does not actively control adverse environmental effects from economic growth. Economic and class division amongst indigenous Fijians has shaped the state's environmental management. Fiji has a hierarchical, hereditary chiefly system promoted as the basis of collective identity and culture, and a wise, unifying and stabilising influence. The systems of land tenure and rent distribution for native land leases adopted by the colonial administration have made many chiefs wealthy, and many have participated in commerce. Many have also held political power. These chiefly élite have a vested interest in both economic development and the political, land tenure and rent distribution systems. They have been able to use these systems to manipulate public opinion within their own institutions and land-owning constituencies. The state has applied environmental management in ways that meet the basic expectations of a modern state, while at the same time ensuring its efforts do not threaten its power base among the indigenous Fijians by bringing the communal ideal into conflict with the discourse of economic development.
Keywords: Environmental management, Fiji; Environmental policy, Fiji; Environmental planning, Fiji; South Pacific Regional Environment Programme (SPREP); Fiji; Sustainable development